Strategies to Optimise Tuber Crops Based Cropping Patterns in Tribal Areas to Ensure Livelihood Security - Indu, M R (JOURNAL OF ROOT CROPS, 2017)
The celebrated Kerala model of development has not made much change for the socio economic life of the marginalized sections of Kerala. The key issues in tribal development are malnutrition and health problems, declining employment opportunities, land alienation, food insecurity and reduced food basket. These problems are due to loss of traditional shifting cultivation and loss of traditional food items such as ragi, chama, cholam, tubers roots etc. Food security is one of the best ways to attain livelihood security.